Radiation‐associated sarcomas other than malignant peripheral nerve sheath tumours demonstrate loss of histone H3K27 trimethylation†. Issue 2 (6th October 2020) - Panse, Gauri; Mito, Jeffrey K; Ingram, Davis R; Wani, Khalida; Khan, Samia; Lazar, Alexander J; Doyle, Leona A; Wang, Wei‐Lien
Abstract : Background and aims: Complete loss of histone H3 lysine 27 trimethylation (H3K27me3) has recently emerged as a biomarker for malignant peripheral nerve sheath tumours (MPNST). Loss of H3K27me3 staining has also been reported in post‐radiation MPNST; however, it has not been evaluated in a large series of radiation‐associated sarcomas of different histological subtypes. The aim of this study was to assess H3K27me3 labelling by immunohistochemistry in radiation‐associated sarcomas and to determine the prevalence of H3K27me3 loss in these tumours. Methods and results: Radiation‐associated sarcomas ( n  = 119) from two tertiary care referral centres were evaluated for loss of H3K27me3, defined as complete loss of staining within tumour cells in the presence of a positive internal control. Twenty‐three cases (19%) showed H3K27me3 loss, including nine of 10 (90%) MPNST, seven of 77 (9%) undifferentiated spindle cell/pleomorphic sarcomas, five of 25 (20%) angiosarcomas, one of five (20%) leiomyosarcomas and one of two (50%) osteosarcomas. Conclusions: Complete H3K27me3 loss was present in 19% of radiation‐associated sarcomas in our series. Our findings demonstrate that loss of H3K27me3 is not specific for radiation‐associated MPNST and may also occur in other histological subtypes of RAS, including radiation‐associated undifferentiated spindle cell/pleomorphic sarcoma, angiosarcoma, leiomyosarcoma and osteosarcoma.